Systematic Review: Research Developments in the Application of the Merdeka Curriculum in Physics Learning (Since 2015-2024) - Rizaldi, Dedi Riyan Rizaldi; Ziadatul Fatimah (Balai Diklat Keagamaan Denpasar, 2025)
The Merdeka curriculum is the latest curriculum applied to the education system in Indonesia. This curriculum will certainly be implemented in all areas or aspects of learning including physics subjects or contexts. The purpose of this study is to identify and analyze the development of research related to the implementation of the Merdeka curriculum in physics learning in Indonesia. This research is a quantitative study with a descriptive and evaluative approach. Research data was obtained through the Dimension.ai feature in the time span from 2015-2024. Research data were analyzed using bibliometric analysis and visualization methods using the VOSviewer application. Based on the data analysis carried out, it is known that research related to the implementation of the Merdeka curriculum in physics learning has increased until 2023, then decreased in 2024. The distribution of the most research files was found in the form of articles with a total of 60 research titles. With these findings, it is clear that the implementation of the Merdeka curriculum in physics learning is still very minimal so that various studies related to this topic become reference opportunities to be applied and carried out so that they are able to represent the main objectives of implementing the Merdeka curriculum in physics learning